Assessment of coping capacity of public health facilities with health emergency situations during an event of flood in Mumbai - Shabana Khan; Dilip Kumar; Navya Vyas (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Floods had been a repeated phenomenon in India, causing considerable losses to properties, life and infrastructure, and public utilities. Floods are found to be a common natural disaster occurring not only in developing countries but also in developed nations. Hospital preparedness against disaster could help in the management of the surge of patients in an effective manner. This study aims to assess the capacity of public health facilities for coping up with health emergency situations during an event of flood in Mumbai. MATERIALS AND METHODS: A cross-sectional study was conducted among 38 public health facilities in Mumbai. A purposive sampling technique was used for the selection of the health facilities. Administrative staff, medical officers, and pharmacy in charges were included in the study. RESULTS: The study revealed that surge capacities in hospitals were adequate as they had additional beds for monsoon-related diseases for the preceding flood situation. There was a triage policy, and the staff were trained on the same. Procurement of drugs was easy because of a good networking system between hospitals. Due to this networking system, patients were also transferred to the nearest healthcare facility in a short span of time. CONCLUSION: The response during an event of a flood in the health facilities of Mumbai city was good as they have regular training sessions to be prepared for the emergency situations during monsoon as they have repeated exposure to floods.